Shāmāṃ dā sūraja, arathāta, Jīwana Sa. Shāma Siṅgha Aṭārī Wālā : Sikha rāja de dama-toṛana dī tasawīra - Zakhamī, Karama Siṅgha (SAMP early 20th-century Indian books project, 1946)
Biography of Shāma Siṅgha Aṭārīwālā, 1788?-1846, Sikh general.